Evaluation of N-methyl-2-pyrrolidone concentration on synthesis and characterization of 1% toluene-4-sulfonic acid monohydrate doped polyaniline Film - Beygisangchin, Mahnoush; Abdul Rashid, Suraya; Shafie, Suhaidi; Lim, Hong Ngee (Springer Science and Business Media LLC, 2023)
Polyaniline (PANI) is one of the most promising conducting polymers to be used in several applications, owing to its easily synthesized, high surface area, cost-effectiveness, and tremendous electrical conductivity. In this research, 1 toluene-4-sulfonic acid monohydrate (PTSA) doped PANI film was fabricated using twelve different concentrations from 0.5 to 6 wt contents of N-methyl-2-pyrrolidone (NMP) as a solvent since the amount of NMP is still a vital aspect to recognize optimum combination. The chemical, optical, thermal, morphological, and electrical conductivity properties are investigated through Fourier transform infrared (FT-IR) spectroscopy, photoluminescence (PL) spectroscopy, ultraviolet-visible (UV“vis) spectroscopy, thermal gravity analysis (TGA), field emission scanning electron microscopy (FE-SEM) and Breuneur“Emmet“Teller (BET), then the four-point probe method. The existence of a hydrogen (H) bonding association between the C=O functional group within NMP and the N“H functional group throughout the PANI films will be shown using FT-IR analysis. Bandgap and PL intensity decreased with increasing NMP concentrations. FE-SEM displays the high-quality morphology of PANI can be achieved by increasing NMP concentrations. The specific electrical conductivity of prepared samples did not significantly change. The 1 PTSA and 3 NMP doped PANI is introduced as optimized PANI film with a low bandgap value of 2.54 (eV), high PL intensity, high specific surface area value of 121.457 (m2/g), and stable conductivity value of 2.45 ( cm)ˆ’1 owing to the arranged design of benzenoid and quinoid parts in its structure which seems a proper candidate to improve PANI film properties for use in sensing and supercapacitor applications.